Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000315129
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Threshold and Subthreshold Anorexia Nervosa: A Three-Year Follow-Up Study

Abstract: Background: Few long-term follow-up studies have evaluated the response to psychotherapeutical interventions in anorexia nervosa (AN). The effectiveness of individual cognitive-behavioral therapy (CBT) and the possible predictors of outcome in outpatients suffering from threshold and subthreshold AN (s-AN) were evaluated. Methods: At the beginning (T0) and at the end of treatment (T1), and 3 years after the end of treatment (T2), 53 subjects with AN and 50 with s-AN (all DSM-IV criteria except amenorrhea or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 110 publications
3
50
0
3
Order By: Relevance
“…shape, weight) in determining a different course of patients with EDs, in terms of response to treatment and long-term outcome [15,54]. This study suggests that a specific disorder of lived corporeality might help to explain why persons with EDs overvalue their body shape and weight.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…shape, weight) in determining a different course of patients with EDs, in terms of response to treatment and long-term outcome [15,54]. This study suggests that a specific disorder of lived corporeality might help to explain why persons with EDs overvalue their body shape and weight.…”
Section: Resultsmentioning
confidence: 94%
“…According to this theory, different studies found that severe concerns about body shape and weight can play a significant role in the persistence of EDs [6,7,8,9,10,11]. Furthermore, shape and weight concerns have been associated with different responses to psychological treatment in several reports [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…In terms of sample selection, for almost all of the older studies the inclusion criterion for patients was underweight. However, underweight is no longer a necessary inclusion criterion for AN as some recent studies included eating disorders not otherwise specified (EDNOS) or partially recovered patients as well [14,28,97]. This may clinically be meaningful, as patients with a BMI of 18 may show all other symptoms of AN and be as impaired as patients fulfilling all criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, a large body of literature has focused on the relationships between eating disorder symptomatology and the beliefs and emotions related to the body [6,7,8,9,10]. As a whole, the data obtained suggest that excessive concerns, overvaluation and uneasiness about the body, its shape and weight are among the main psychopathological features that favor the onset and maintenance of eating disorders.…”
Section: Introductionmentioning
confidence: 99%